A Community Satisfaction Index on Health Services in Siti Aisah Hospital of Lubuk Linggau - Kardila Kardila; Sri Handayani; Abdul Rahman (Journal of Indonesian Management, 2021)
This study aims to determine the index of community satisfaction in health services in Siti Aisyah Hospital of Lubuk Linggau. The analytical method used is the Community Satisfaction Index (CSI) with 9 service elements in accordance with The Minister of State Apparatus Empowerment Regulation and Bureaucratic Reform No. 14 of 2017. The sample in this study amounted to 80 respondents. The results showed that service satisfaction in Siti Aisyah Hospital of Lubuk Linggau was good, it could be seen that the high of the Community Satisfaction Index score was 82,672 which included in the service quality category was "B", which means the service quality was good of the nine service elements used. Cost/tariff is the service element with the highest index value with a CSI value of 3.53 with a CSI conversion value of 88.13 with a good performance category. While the element with the lowest index value is the behavior of the implementer with an IKM value of and low indicator with an average value of 3.06, the CSI conversion value of 76.56 is found in the behavior of the implementer with a good category.